Mitochondrial transfer/transplantation in lung injury: mechanism, therapeutic potential, and clinical application - Wang, Ling-Jie; Guo, Peng-Fei; Zhang, SongOu; Wang, Sai; Chen, Yi-Zhao; Yan, Hong-Wang; Zhang, Xue-Lin (Frontiers in Immunology, 2025)
Lung injury has become a critical clinical problem that urgently requires resolution due to its high morbidity, high mortality, and the limitations of existing treatment methods. Mitochondrial dysfunction, as the core mechanism of lung injury, promotes disease progression through energy metabolism imbalances, oxidative stress, and exacerbated inflammatory responses. Recent studies have found that intercellular mitochondrial transfer, acting as a “transcellular rescue” mechanism, can deliver functional mitochondria through pathways such as tunneling nanotubes, exosome. This process provides a novel approach to replenish energy for damaged cells, regulate inflammation, and repair tissues. In various lung injury models, mitochondrial transfer/transplantation has been shown to improve alveolar-capillary barrier function, reduce collagen deposition, inhibit the release of inflammatory factors, and restore mitochondrial membrane potential. This is particularly evident in conditions such as acute lung injury, pulmonary fibrosis, acute respiratory distress syndrome, and chronic obstructive pulmonary disease, where it shows significant therapeutic potential. The combination of diverse delivery methods and multi-source mitochondria provide a flexible strategy for clinical application. In summary, mitochondrial transfer, as an emerging intercellular communication and rescue mechanism, provides a promising new direction for the precision treatment of lung injury.